Cost-Effective and Reliable Sidechain Approach for Managing Small-Scale Digital Asset Trading Platforms - Nam-Yong Lee (Applied Sciences)
This study proposes a cost-effective and reliable blockchain-based approach for managing small-scale digital asset trading platforms. Instead of developing an independent blockchain, the proposed method constructs a sidechain anchored to established blockchains known for their stability and reliability, such as Bitcoin and Ethereum. In this study, we refer to these established blockchains serving as the mainchain for our sidechain as the reference chain. The proposed sidechain, termed the platform chain in this paper, inherits the security and trust of the reference chain, while reducing operational costs and requiring no modifications to it. To enhance efficiency and privacy, the proposed method introduces a dual-sidechain architecture. The platform chain can be constructed either as a private blockchain or a consortium blockchain, depending on the specific operational requirements. In this architecture, only the hash values of transactions are recorded on the platform chain by default, while complete transaction content is disclosed through a dual platform chain under controlled conditions. This enables strong privacy guarantees, alongside auditable transparency when needed. To evaluate the security and feasibility of our approach, we perform a comprehensive threat assessment, addressing critical threats such as operator-level manipulation, invalid or harmful user actions, collusion among system entities, and dishonest behavior by the auditor. Our results confirm that the proposed sidechain framework provides a secure, scalable foundation for digital asset trading platforms, effectively enhancing privacy and ensuring robust protection under various adversarial conditions.